Development of medical informatics in China over the past 30 years from a conference perspective and a Sino-American comparison - Liang, Jun; Wei, Kunyan; Meng, Qun; Chen, Zhenying; Zhang, Jiajie; Lei, Jianbo (PeerJ, 2017)
Background As the world’s second-largest economy, China has launched health reforms for the second time and invested significant funding in medical informatics (MI) since 2010; however, few studies have been conducted on the outcomes of this ambitious cause. Objective This study analyzed the features of major MI meetings held in China and compared them with similar MI conferences in the United States, aiming at informing researchers on the outcomes of MI in China and the US from the professional conference perspective and encouraging greater international cooperation for the advancement of the field of medical informatics in China and, ultimately, the promotion of China’s health reform. Methods Qualitative and quantitative analyses of four MI meetings in China (i.e., CMIAAS, CHINC, CHITEC, and CPMI) and two in the US (i.e., AMIA and HIMSS) were conducted. Furthermore, the size, constituent parts and regional allocation of participants, topics, and fields of research for each meeting were determined and compared. Results From 1985 to 2016, approximately 45,000 individuals attended the CMIAAS and CPMI (academic), CHINC and CHITEC (industry), resulting in 5,085 documented articles. In contrast, in 2015, 38,000 and 3,700 individuals, respectively, attended the American HIMSS (industry) and AMIA (academic) conferences and published 1,926 papers in the latter. Compared to those of HIMSS in 2015, the meeting duration of Chinese industry CHITEC was 3 vs. 5 days, the number of vendors was 100 vs. 1,500+, the number of sub-forums was 10 vs. 250; while compared to those of AMIA, the meeting duration of Chinese CMIAAS was 2 vs. 8 days, the number of vendors was 5 vs. 65+, the number of sub-forums was 4 vs. 26. HIMSS and AMIA were more open, international, and comprehensive in comparison to the aforementioned Chinese conferences. Conclusions The current MI in China can be characterized as “hot in industry application, and cold in academic research.” Taking into consideration the economic scale together with the huge investment in MI, conference yield and attendee diversity are still low in China. This study demonstrates an urgent necessity to elevate the medical informatics discipline in China and to expand research fields in order to maintain pace with the development of medical informatics in the US and other countries.
Keywords: Medical informatics; Health information technology; Conference; Meeting proceedings; Sino-american comparison